CHARACTERISTICS OF VEGETABLE OILS FOR USE AS FUEL IN STATIONARY DIESEL ENGINES - TOWARDS SPECIFICATIONS FOR A STANDARD IN WEST AFRICA - (:unkn) unknown (My University, 2013)
West African countries are increasingly interested in producing straight vegetable oil (SVO) for direct use as fuel in diesel engines for stationary applications in the fields of agriculture, power generation and industry. Straight vegetable oil fuel quality, i.e impurities content and physico-chemical properties, is a recurring issue that seriously impedes the development of the sector. However, there is still no standard defining the quality characteristics of vegetable oils for fuel purposes in stationary engines. The aim of this study was to propose a quality standard with a set of specifications (parameters, test method, limit value), which SVOs must comply with in order to be used as fuel in stationary diesel engines without causing breakdowns or serious lifetime reductions. After a brief review of SVO production and use techniques, we present a critical review of existing fuel standards (fossil fuels, biodiesel and European SVO) that must be adapted to the use of SVO for stationary engines, with regard to the requirements of engine manufacturers. Based on this critical analysis and current knowledge of vegetable oil characterization, we propose a simplified, inexpensive and efficient basic standard of seven specifications. This standard enables easy assessment of SVO quality for fuelling a stationary diesel engine.
Keywords: African Research